2005
DOI: 10.1097/01.ta.0000175087.64842.d1
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Change and the Role of Inpatient Counseling for Alcohol/Substance Abusing Youth With Major Trauma

Abstract: Although findings regarding the assessment of attitudes toward readiness to change among young drug/alcohol-using patients experiencing penetrating trauma were initially very encouraging, facilitating and engaging these patients in actual behavior changing activities was far more challenging. Further exploration into the existing barriers to accessing treatment services and cultivating attitudes toward changing substance use behaviors is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Some trauma centers have implemented screening and intervention programs for heavy alcohol use, [16][17][18][19][20] and initial successes have been demonstrated. 16,[18][19][20][21][22] The finding that patients with repeat trauma were more likely to use tobacco and recreational drugs and were more likely to use drugs on the day of injury calls into question the responsibility these patients have in managing their health and behavior. Further, in addition to the patients identified in the current study, it is important to consider potential injury to others (eg, bystanders).…”
Section: Discussionmentioning
confidence: 99%
“…Some trauma centers have implemented screening and intervention programs for heavy alcohol use, [16][17][18][19][20] and initial successes have been demonstrated. 16,[18][19][20][21][22] The finding that patients with repeat trauma were more likely to use tobacco and recreational drugs and were more likely to use drugs on the day of injury calls into question the responsibility these patients have in managing their health and behavior. Further, in addition to the patients identified in the current study, it is important to consider potential injury to others (eg, bystanders).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies find that the SOCRATES does predict treatment entry, 36 others do not. 37 For example, Yonas and colleagues, found that although 85% of trauma patients with positive drug screens were in the contemplative or action-oriented stages with regard to their substance abuse, 0% initiated substance abuse treatment postdischarge. 37 However, it is possible that this measure may be useful as a starting place for brief motivational interventions to encourage treatment linkage.…”
Section: Discussionmentioning
confidence: 99%
“…37 For example, Yonas and colleagues, found that although 85% of trauma patients with positive drug screens were in the contemplative or action-oriented stages with regard to their substance abuse, 0% initiated substance abuse treatment postdischarge. 37 However, it is possible that this measure may be useful as a starting place for brief motivational interventions to encourage treatment linkage. Our finding that pre-baseline use of formal treatment services was not a significant predictor of service use in the follow-up period is not consistent with the findings from prior studies conducted in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…While the literature on classifying patients into stages of change is not entirely consistent (Carey, Purnine, Maisto, & Carey, 1999), prior studies have suggested that patients often fit into one of three ordinal categories: Precontemplation (not even considering decreasing substance use), Contemplation (considering decreasing substance use), and Action (taking steps to decrease substance use). The literature on readiness to change has primarily focused on adults, and the available studies on adolescents have largely included hospitalized and/or incarcerated youths with severe substance-related difficulties (Barnett et al, 2002; Slavet et al, 2006; Yonas et al, 2005). Therefore, little research has been completed using this three-stage framework with a primary care system’s teenage population, which consists of youths typically engaging in less serious forms of substance use.…”
Section: Introductionmentioning
confidence: 99%